LITERATURE STUDY THE RELATIONSHIP BETWEEN PREGNANT WOMEN'S KNOWLEDGE ABOUT NUTRITION AND THE INCIDENCE OF CHRONIC ENERGY DEFICIENCY (CED) - Mulyani, Dera Tri; Mulyani, Sri; Yuliana, Yuliana (Jurnal Keperawatan Universitas Jambi, 2024)
The results of the Basic Health Research (Riskesdas) show that the prevalence of the risk of CED in pregnant women is still quite high at 17.3%, for the age that often occurs is 15-49 years. One of the factors causing Chronic Energy Deficiency (KEK) is knowledge, pregnant women who have good knowledge will tend to pay attention to the nutritional value of the food consumed. The purpose of the study was toanalyze research articles related to the relationship between knowledge of pregnant women about nutrition and the incidence of KEK. Thisstudy uses a literature review research method with 11 articles obtained through screening based on the criteria set by the researcher. Search articles using Google Schoolar and Semantic Sholar databases. The conclusion of this study is that mothers who have good knowledge about nutrition do not experience CED, while pregnant women who have less knowledge about nutrition are at risk of experiencing CED.